Purchasing decisions through food delivery applications among gen Z: A UTAUT2 approach - Fitri Yutika; Sihombing, Daniel Oktodeli; Tan, Petrus Sentoso (SEAN Institute, 2024)
This study investigates the factors influencing food purchasing decisions through Food Delivery Applications among Generation Z, with a focus on students at the Institut Teknologi dan Bisnis Sabda Setia Pontianak. Utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) as the theoretical framework, data from 125 Gen Z students were analyzed. The findings reveal that habits and price value significantly influence behavioral intentions, impacting the usage of FDAs. However, factors like performance expectations, effort expectations, facilitating conditions, hedonic motivation, and social influence did not exhibit significant effects. These findings provide crucial insights for food delivery service providers to adapt marketing strategies and service development according to the preferences of Gen Z consumers. By focusing on habits and pricing, this research can serve as a foundation for developing more effective and relevant business strategies targeting the Gen Z market.